Missing‐Linker‐Confined Single‐Atomic Pt Nanozymes for Enzymatic Theranostics of Tumor. (31st March 2023) - Wang, Dongdong; Zhang, Lei; Wang, Changlai; Cheng, Zhiyu; Zheng, Wei; Xu, Pengping; Chen, Qianwang; Zhao, Yanli
Abstract: Conventional nanozymes often possess low active site density. Pursuing effective strategies for constructing highly active single‐atomic nanosystems with maximum atom utilization efficiency is exceptionally attractive. Herein, we develop a facile "missing‐linker‐confined coordination" strategy to fabricate two self‐assembled nanozymes, i.e., conventional nanozyme (NE) and single‐atomic nanozyme (SAE), which respectively consist of Pt nanoparticles and single Pt atoms as active catalytic sites anchored in metal–organic frameworks (MOFs) with encapsulated photosensitizers for catalase‐mimicking enhanced photodynamic therapy. Compared to a Pt nanoparticle‐based conventional nanozyme, a Pt single‐atomic nanozyme shows enhanced catalase‐mimicking activity in generating oxygen for overcoming tumor hypoxia, thus exhibiting a more efficient reactive oxygen species generation and high tumor inhibition rate. Abstract : A self‐assembled single‐atomic Pt nanozyme was developed using a facile missing‐linker‐confined coordination strategy. The nanozyme shows superior catalase‐mimicking activity for the catalytic conversion of H2 O2 overproduced in tumors into localized O2 for tumor hypoxia alleviation, which leads to enhanced ROS generation from loaded photosensitizers for apoptotic cancer cell death.